O planejamento urbano e os acidentes de trânsito: um estudo sobre o município de Toledo PR - Ruschel, Andressa Carolina (2016)
This research dissertation aimed to analyze how urban planning influenced on traffic accidents caused in the 2011-2015 period in the urban area of the municipality of Toledo - PR; it describes the evolution of urban development of cities from the theories of spatial analysis and urban planning; it identifies, maps and determine the frequency with which they occur traffic accidents in Toledo - PR in the 2011-2015 period; and finally, it characterizes the critical points. It is justified by the high traffic accidents rate in Toledo, which occupies the 8th position in Parana in Quantitative Victims of Homicide Traffic. The rapid urbanization and the continuous increase of the vehicle fleet contributed to the growth of traffic accidents in Toledo, which had no proper planning of urban space. The methodology used was through theoretical substantiation of spatial analysis and urban planning; primary data collection in Traffic Accident Occurrence Reports then tabulated and analyzed as theoretical foundation. It was possible to verify that the highest traffic accident rate is in the center of the city, opening hours trade and services, which coincides with the high density of people and vehicles, located in the central area. Urban planning can interfere with the accident problem, with plans to decentralize business activities, encourage the disuse of the automobile and promote spaces suitable for foot traffic and cyclists, for mobility and sustainable urban spaces.